Application of Virtual Simulation in Biology Learning Evaluation of Impact on Concept Understanding by Agrotechnology Students - Riyanti (PT. Anagata Sembagi Education, 2024)
This study aims to evaluate the impact of implementing virtual simulation in Biology learning on concept understanding by Agrotechnology students. Along with the development of technology, technology-based learning, especially virtual simulation, has begun to be applied to support the understanding of more complex concepts. Although a number of previous studies have shown the successful use of virtual simulations in various disciplines, there are still research gaps that need to be filled regarding the application of virtual simulations in the context of Biology education, especially in Agrotechnology study programs. This creates a phenomenon where students have difficulty in understanding these concepts. This research fills the gap by evaluating the application of virtual simulation as a learning method in overcoming this challenge. Using an experimental method, this study involved 30 students as samples, who were tested using pretest and posttest to measure the improvement of their understanding of Biology concepts. The results of the analysis showed that the application of virtual simulation resulted in a significant increase in students' understanding, which was reflected in the N-gain score with an average of 78.25. This value indicates a substantial increase in understanding of Biology concepts after using virtual simulation as a learning method. This finding supports the effectiveness of virtual simulation in improving the understanding of complex concepts, so it can be an effective alternative in learning in Biology. The results of this study provide positive implications for the use of technology in education, especially in improving the quality of learning in higher education